(untitled) (Signifikan: Jurnal Ilmu Ekonomi, 2021)
Although the Yogyakarta Special Region and Central Java are two independent provinces with different regulations, these economies were integrated as a unity that interacts with each other, so this study examined whether the growth spillovers between regencies/cities occurred in these provinces. The data included economic growth, education, working-age population, and asphalted road published by the Central Bureau of Statistics for 2001-2018. This study used a regression analysis based on the Dynamic Ordinary Least Square (DOLS) model. The results showed that there were growth spillovers. The economic growth of a regency/city was positively influenced by economic growth in its surrounding regions. A particular regency/city obtained benefit from economic growth occurred in its surrounding. Meanwhile, an increase in the working-age population and the asphalted road positively affects economic growth. However, the increase in education did not affect economic growth. Therefore, the local government needs to improve connectivity between regions by building road networks and enhancing intergovernmental cooperation. JEL Classification: J6, O1, R1 How to Cite: Susanto, J., & Udjianto, D. W. (2021). Do Growth Spillovers Matter?. Signifikan: Jurnal Ilmu Ekonomi, 10(1), 31-50. doi: http://doi.org/10.15408/sjie.v9i2.17900.